Diplomasi Indonesia Menghadapi Pembatasan Ekspor Minyak Kelapa Sawit Uni Eropa, Studi Kasus: Renewable Energy Directive II (RED) II, 2018-2023 - Asila Ghina Rahmani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The European Union has issued a Renewable Energy Directive II (RED II) policy that seeks to gradually reduce the use of palm oil-based biofuels by 2030. This policy has triggered major challenges for Indonesia as the world's leading palm oil producer, including significant economic and social impacts. In facing this policy, Indonesia has implemented a diplomatic strategy to maintain market access and protect national interests. This research aims to determine the process of Indonesian diplomacy towards the European Union regarding restrictions on palm oil exports in the RED II policy. This research uses qualitative data collection techniques through literature studies and interviews. The diplomatic process carried out is analyzed using diplomacy and stimulus-response theory. The stimulus from the RED II policy, which contains economic, political, and environmental pressures, encourages Indonesia to respond through strategic diplomatic steps, including bilateral negotiations, filing disputes at the World Trade Organization (WTO), and efforts to build a sustainability narrative through multilateral forums. The results show that despite political and economic challenges, Indonesia is able to dynamically adjust its response, both through diplomacy and bilateral negotiations, to maintain the position of palm oil as a sustainable product and secure its strategic role in the global market.